2018
DOI: 10.1155/2018/6140381
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes and Factors Associated with Revision Surgery for Metastatic Disease of the Spine

Abstract: Study Design Retrospective review of a prospective database. Objective Certain subset of patients undergoing surgical treatment for spinal metastasis will require a revision surgery in their disease course; however, factors predictive of revision surgery and survival outcomes are largely unknown. The goal of this study is to report on survival outcomes as well as factors predictive of revision surgery in this unique patient population. Methods A total of 55 patients who met the inclusion criteria were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…of stay, and morbidity to the operation, and it decreases spinal column stability. 6,7 Surprisingly, the overall incidence of corpectomy and instrumentation is extremely high in this study (55.4% and 97.1%, respectively), and it is not matching with the literature. Although the authors did not provide clear explanation about this discrepancy in the discussion, the presence of spinal instability either due to multiple-level pathological vertebral fractures or multiplelevel surgical decompression might provide some justification.…”
Section: Fundingcontrasting
confidence: 85%
See 1 more Smart Citation
“…of stay, and morbidity to the operation, and it decreases spinal column stability. 6,7 Surprisingly, the overall incidence of corpectomy and instrumentation is extremely high in this study (55.4% and 97.1%, respectively), and it is not matching with the literature. Although the authors did not provide clear explanation about this discrepancy in the discussion, the presence of spinal instability either due to multiple-level pathological vertebral fractures or multiplelevel surgical decompression might provide some justification.…”
Section: Fundingcontrasting
confidence: 85%
“…For example, performing transpedicular decompression adds more complexity, operative time, blood loss, length of stay, and morbidity to the operation, and it decreases spinal column stability. 6,7…”
mentioning
confidence: 99%
“…The stability of a spinal construct is dependent on achieving a timely bony fusion [ 12 ]. Local and systemic effects of spine tumors do not favor this outcome [ 2 , 14 ]. In addition, oncological patients often have a poor mobility and nutrition, and frequently undergo radiation and chemotherapy, which would further compromise the fusion bed [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality after surgery for spinal tumors depends on a variety of factors, including patient age, comorbidities, and tumor type [ 33 ]. Prior research has shown a longer median survival rate for patients who undergo a revision surgery versus those who do not [ 14 ]. Patients in our study with hardware failures had longer overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical revision rate in this study was consistent with previous reports in the literature ranging from 10.7% to 22%. 30,31 In the KþE group, only 2 patients were revised with surgical decompression and stabilization due to progressive neurologic deficits related to tumor progression. No patients in the SþE or KþE underwent repeat treatment for persistent pain alone.…”
Section: Discussionmentioning
confidence: 99%